AN IMPLEMENTATION OF GOLD INVESTMENT IN MALAYSIA: A CONTEMPORARY PRACTICE AT BANKING INSTITUTION AND NON-BANKING INSTITUTION - Raudzatul Jannah Ezahar; Mohd Sollehudin Bin Shuib; Ahmad Khilmy Bin Abdul Rahim (Journal of Islamic, Social, Economics and Development, 2021)
The purpose of this study is to examine the characteristics of Islamic gold practice in Malaysia by comparing mean differences and similarities practice from different two institutions Bank Muamalat Malaysia Berhad (BMMB) and non-banking institution, Public Gold in their practicing of gold investments in contemporary days. This research adopts a qualitative study using the purposive sampling and interview technique of Public Gold (PG) as a pioneer gold trading company in Malaysia and Islamic bank institution Bank Muamalat Malaysia Berhad (BMMB). The research discovered that Public Gold and Bank Muamalat offered two types of gold investment which are physical gold and gold saving accounts. For the gold saving account PG namely Gold Accumulation Program (GAP) and BMMB Muamalat Gold–i purposely initiated for investment planning. The actual implementations have shown there were similarities characteristics within both products (GAP) and Muamalat Gold-i from aspects of gold-standard requirements and their fulfilled obligation of Shariah principles.